2016
DOI: 10.1007/s00262-016-1793-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the murine H-2Db and human HLA-A*0201 MHC class I-restricted HPV6 E7-specific cytotoxic T lymphocyte epitopes

Abstract: Recurrent Respiratory Papillomatosis (RRP) is caused by human papillomavirus (HPV) infection, most commonly types-6 (HPV-6) and -11 (HPV-11). Due to failed host immune responses, HPV is unable to be cleared from the host, resulting in recurrent growth of HPV-related lesions that can obstruct the lumen of the airway within the upper aerodigestive tract. In our murine model, the HPV-6b and -11 E7 antigens are not innately immunogenic. In order to enhance the host immune responses against the HPV E7 antigen, we l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…HEK 293 expi cells were acquired from ATCC (Manassas, VA). The generation of 293 cells expressing the murine MHC class I molecule D b , 293-D b , or K b , 293-K b , was described previously (78). 293 expi, 293-Db, and 293-K b cells were cultured in Dulbecco's modified Eagle medium (DMEM) containing 2 mM glutamine, 1 mM sodium pyruvate, 100 IU ml 21 penicillin, 100 mg ml 21 streptomycin, and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…HEK 293 expi cells were acquired from ATCC (Manassas, VA). The generation of 293 cells expressing the murine MHC class I molecule D b , 293-D b , or K b , 293-K b , was described previously (78). 293 expi, 293-Db, and 293-K b cells were cultured in Dulbecco's modified Eagle medium (DMEM) containing 2 mM glutamine, 1 mM sodium pyruvate, 100 IU ml 21 penicillin, 100 mg ml 21 streptomycin, and 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…293-D b cell line has been previously described [ 14 ]. 293-D b cells were cultured in DMEM medium supplemented with 2 mM glutamine, 1 mM sodium pyruvate, 100 U/mL penicillin, 100 μg/mL streptomycin, and 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…These data confirm previous findings using a DNA vaccine targeting HPV11 E6E7 that was not linked to CRT. 4 Although it is possible to induce an E7 response to vaccination by designing a vaccine containing only E7, 6 it appears that in the C57BL/6 background, E6 is the dominant immunologic antigen when both E6 and E7 proteins are expressed together. Vaccines designed for human use often include both antigens, to maximize the chances for antigen presentation, and there are many trials currently underway in HPV-associated diseases.…”
Section: Prophylactic Vaccines Against Low-and High-riskmentioning
confidence: 99%
“…In this report, it was demonstrated that E6 is the immunodominant peptide, but no specific immunologic response was seen against E7. One strategy to enhance immunologic responses and antigen presentation is linkage of the antigen of interest to calreticulin (CRT), and we then showed that linking CRT to HPV6‐E7 could generate an immune response against HPV6‐E7 not present in the non–CRT‐linked vaccine . However, the gold standard test for the efficacy of DNA vaccines is the ability to control growing tumors in vivo that express the target antigen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation